INTEGRATION OF FOLK ORAL LITERATURE AND EDUCATION: A CASE STUDY OF QO‘QON CITY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This research investigates the integrative potential of Uzbek folk oral literature within contemporary educational processes, using Qo‘qon City as a regional case study to demonstrate the pedagogical, cultural, communicative, and value-forming advantages of incorporating folk narratives, rituals, proverbs, epic poetry, and children’s folklore into formal and informal instruction. While folk literature historically functioned as the primary transmitter of moral norms, identity, memory, and intergenerational knowledge across Central Asia, modern schooling often marginalizes these native epistemologies in favor of technocratic standardized content, resulting in weakened cultural continuity and reduced engagement among learners. Through qualitative fieldwork, participant observation, narrative analysis, and interviews with educators, local folklorists, community elders, and students in Qo‘qon, the paper identifies specific integrative strategies, curriculum models, and pedagogical techniques that successfully merge oral tradition with contemporary teaching goals. The findings demonstrate that thoughtfully applied folklore-based instruction enriches critical thinking, emotional intelligence, ethical reasoning, creativity, and cultural awareness more effectively than textbook-only education. This study concludes with recommendations for curriculum design, teacher training, digitization efforts, and community-school partnerships aimed at institutionalizing a sustainable folk-education integration model across Uzbekistan.